Proposta para configuração de operação logística em centros de distribuição - Toso, Milton Ramos (2014)
The main purpose of this dissertation is to propose a methodology framework using multicriteria decision-making method, Analytic Hierarchy Process (AHP), to define the configuration of logistics operations at the distribution centers in the Brazilian retail market. This framework is based on an approach in which the choice of operational alternatives used in the internal activities of a distribution center (receiving, storage, picking and shipping) depend on the distribution strategy as well as the attributes and requirements of the business environment of the company. In order to develop this work, a bibliographic research has been performed in the following fields: logistics and distribution strategy, functions, activities and management of distribution centers and decision-making. It has been carried out interviews in the research field with the high management representatives from large logistics providers with the aim of determining which business requirements might be considered in the approach. The interviews have been also important to determine the preferences and weights to the attributes used for decision-making. The proposed framework has been also used in a case study in order to validate the attributes and has served too as a basis to compare the preferences of the managers of the logistic providers and of the manager of the studied company, regarding the configuration of the logistic operations. This framework has been validated, the preferences among decision makers have been similar, except at the weight between the attributes of operational and investment costs. In general, this framework has validated the results and has proved to be a useful tool to support decision-making process in a real situation and also has generated scenarios and sensitivity analysis to the decision maker.